The Role of Physical Education in Promoting Lifelong Fitness: A Review of Contemporary - Srinivasan, J. P. Desiga (AG Volumes, 2025)
Beyond encouraging physical health, physical education improves students' cognitive, emotional, and interpersonal skills as well as their life skills, including problem-solving, discipline, and collaboration. Examine the many studies on the topic of physical education's function in fostering lifelong fitness and modern methods in this page. Through the development of healthy behaviors, physical literacy, and general well-being, physical education is essential in supporting lifetime fitness, as this review emphasizes. A comprehensive PE curriculum aligned with national standards, combined with wellness education, empowers students to make informed health decisions. Integrating diverse, engaging activities and non-traditional sports appeals to varied interests, encouraging sustained participation. Family and community involvement, themed events, and the use of technology further enhance student engagement. Ongoing professional development for educators ensures effective instruction and innovation. By creating supportive, inclusive environments and linking physical activity to broader educational goals, schools can cultivate lifelong fitness and holistic development.